2008
DOI: 10.1167/iovs.07-0786
|View full text |Cite
|
Sign up to set email alerts
|

Monosomy of Chromosome 3 and an Inflammatory Phenotype Occur Together in Uveal Melanoma

Abstract: Monosomy 3 in uveal melanoma is associated with the presence of an inflammatory phenotype, consisting of a high HLA class I and II expression as well as an increased number of tumor-infiltrating macrophages. In a multivariate Cox regression analysis, the presence of monosomy 3 was one of the best prognostic markers of metastatic disease and survival, although the follow-up time was short.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
125
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 28 publications
2
125
2
Order By: Relevance
“…In uveal melanoma, however, an inflammatory phenotype is associated with a poor outcome and has been found to be associated with loss of one chromosome 3. 18 Uveal melanoma may show increased numbers of CD3 þ T lymphocytes and CD11b þ macrophages. 19 High densities of inflammatory cells occur more frequently in epithelioid-cell-type tumours, which are especially the tumours with chromosome 3 loss.…”
Section: Prognostic Impact Of Intratumoral Immune Infiltratesmentioning
confidence: 99%
See 1 more Smart Citation
“…In uveal melanoma, however, an inflammatory phenotype is associated with a poor outcome and has been found to be associated with loss of one chromosome 3. 18 Uveal melanoma may show increased numbers of CD3 þ T lymphocytes and CD11b þ macrophages. 19 High densities of inflammatory cells occur more frequently in epithelioid-cell-type tumours, which are especially the tumours with chromosome 3 loss.…”
Section: Prognostic Impact Of Intratumoral Immune Infiltratesmentioning
confidence: 99%
“…19 High densities of inflammatory cells occur more frequently in epithelioid-cell-type tumours, which are especially the tumours with chromosome 3 loss. 18 To understand the cause of the influx of inflammatory cells, one has to study the composition and function of the immune infiltrate, in the context of microenvironmental factors, such as hypoxia. 20 …”
Section: Prognostic Impact Of Intratumoral Immune Infiltratesmentioning
confidence: 99%
“…1 Several histologic prognostic factors have been described for this type of cancer, such as large tumor size, involvement of the ciliary body, extrascleral extension, and an inflammatory phenotype. 2,3 Specific genetic alterations that are significantly associated with the development of metastases have been identified, such as monosomy 3. In spite of the development of very precise techniques for detecting chromosomal alterations, such as spectral karyotyping, fluorescence in situ hybridization (FISH), comparative genomic hybridization, and multiplex ligation-dependent probe amplification (MLPA), loss of a complete chromosome (monosomy 3) is still the most important genetic aberration to predict survival, superior to clinical and pathologic features.…”
mentioning
confidence: 99%
“…Both monosomy 3 analysis using the microsatellite DNA assay and transcriptome profiling have been successfully performed in fine-needle biopsy uveal melanoma specimens taken prior to radiotherapy, and CISH has been shown to work successfully on fine-needle biopsies from breast and lung cancer patients. [28][29][30][31] Previous studies 16,17,23 have shown epithelioid cells to correlate with loss of 1 copy of chromosome 3. In our study, monosomy 3 was detected in 38% of the epithelioid/mixed cell types (Table 5).…”
Section: Commentmentioning
confidence: 99%
“…[15][16][17][18] The dual aim of this study is to adapt the CISH technique to tumor imprints and to lower turnaround time and the costs involved for determining chromosome 3 status in uveal melanoma. Concordance of CISH with 2 current established techniques, FISH and single-nucleotide polymorphism (SNP) array, is evaluated and this method of tumor sampling for the determination of chromosome 3 alterations in uveal melanoma is also discussed.…”
mentioning
confidence: 99%